Analisis Kepuasan Petani Terhadap Pupuk Bersubsidi pada Transaksi Menggunakan Kartu Tani di Kecamatan Gemuh, Kabupaten Kendal - Herinatasya, Angela Anindyta; Mariyono, Joko; Handayani, Migie (Universitas Galuh, 2025)
Subsidized fertilizer is one of the government policies aimed at increasing agricultural productivity. The farmer cards are used to support the implementation of fertilizer subsidies to ensure accurate targeting. Gemuh District recorded the highest number of fertilizer purchase transactions in Central Java Province from January 1 to April 30, 2022. This study aims to assess the effectiveness of subsidized fertilizer use, measure farmers' satisfaction with subsidized fertilizer. The research was conducted in Gemuh District, Kendal Regency from September to November 2024 with a total of 100 farmer respondents The research method employed a case study approach with a quantitative methodology. Data analysis was carried out using descriptive analysis, Importance-Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The CSI analysis results indicate that the farmers' satisfaction level is 81.01%, which falls into the very satisfied category. Attributes in Quadrant I of the IPA analysis include quality, consistency between allocated and received fertilizer, and ease of access to information on subsidized fertilizer availability. Quadrant II includes price, ease of obtaining subsidized fertilizer, and the availability of subsidized fertilizer stock. Quadrant III consists of the consistency of allocation with balanced fertilization recommendations and farmers’ requests. Quadrant IV includes the ease of transactions using the Farmer Cards.